Striking skills: Developing power to turn - Spaniol, F. J. (Strength and Conditioning Journal, 2012)
The purpose of this article was to discuss rotational power and its implications for striking skills and improved sport performance. Topics to be addressed include fundamentals of striking skills, testing, and evaluation, and suggestions for program design.